High accumulation of linezolid and its major metabolite in the serum of patients with hepatic and renal dysfunction is significantly associated with thrombocytopenia and anemia - Junqiang Gou; Qian Li; Ning Fan; Chen Zhang; Haiwen Tang; Xiaofeng Wang; Dongfeng Yin (Microbiology Spectrum, 2025)
ABSTRACT This study aims to examine the serum levels of linezolid and its metabolites (PNU-142300 and PNU-142586) in patients with varying hepatic and renal function. It seeks to understand how these levels relate to thrombocytopenia and anemia and to identify concentration thresholds that could cause these adverse effects, thereby aiding in personalized drug dosing. This prospective study was conducted from January to December 2023. According to the established inclusion and exclusion criteria, 77 patients with infections treated with linezolid were selected as the research subjects. Venous blood samples were collected every 48 h starting from the first use of linezolid, specifically 30 min before the next dose. Laboratory data were obtained through biochemical analysis and blood routine tests, and blood drug concentration monitoring was carried out based on the pre-established high-performance liquid chromatography (HPLC) method. The exposure levels of linezolid and its metabolites in the serum of patients under different liver and kidney function states were compared, and the relationships between these drug exposure levels and platelet count and hemoglobin concentration were analyzed. Additionally, the receiver operating characteristic (ROC) curve was used to determine the blood drug concentration thresholds of linezolid and its metabolites that led to thrombocytopenia or anemia. Finally, survival analysis was used to evaluate the time differences in the occurrence of adverse reactions, such as thrombocytopenia and anemia, between the liver and kidney function impairment group and the normal group after the use of linezolid. Exposure to linezolid and its metabolites increased with the severity of hepatic and renal impairment. Patients with severe and moderate hepatic and renal impairment had a substantially higher median Cmin of linezolid and its metabolites 2 and 3 than those with mild hepatic and renal impairment. The platelet count and hemoglobin concentration were significantly associated with linezolid and its metabolite overexposure. The concentration threshold for linezolid and its metabolites 2 and 3 to cause thrombocytopenia and anemia were 7.0, 3.6, and 4.3 mg/L. Patients with hepatic and renal impairment exhibit higher levels of linezolid and its metabolites, potentially leading to adverse effects like thrombocytopenia and anemia. It is recommended to monitor drug levels and develop individualized dosage regimens.IMPORTANCEThe accumulation of plasma linezolid and its metabolites increased with the degree of liver and kidney injury. High plasma linezolid and its metabolite accumulation is significantly associated with thrombocytopenia and anemia. Linezolid and its metabolite concentration threshold can warn the clinical prevention of hematological adverse reactions. Individual therapy guided by therapeutic drug monitoring (TDM) can improve the efficacy of linezolid and reduce toxic reactions. Patients with severe hepatic and renal dysfunction should actively monitor the blood routine and linezolid concentration and adjust the dosage in time.